Global trends and prospects about synaptic plasticity in Alzheimer’s disease: a bibliometric analysis - Zhang, Yingying; Zhang, Junyao; Wang, Yinuo; Yao, Junyan (Frontiers in Aging Neuroscience, 2023)
Background and purpose In recent years, synaptic plasticity disorders have been identified as one of the key pathogenic factors and the early pathological characteristics of Alzheimer’s disease (AD). In this study, we tried to use bibliometric analysis to gain a systematic understanding about synaptic plasticity in Alzheimer’s disease. Methods We extracted relevant publications from the Web of Science Core Collection (WoSCC) on August 29th, 2022. Then, we used CiteSpace, VOSviewer and other online bibliometric platforms1 to further analyze the obtained data. Results A total of 2,348 published articles and reviews about synaptic plasticity in AD from 2002 to 2022 were identified. During the past two decades, the overall trends of the numbers and citations of manuscripts were on the rise. The United States was the leading country with the largest number of publications which showed its crucial role in this field. The collaboration network analysis showed that the United States and China had the most frequent collaboration. In addition, Harvard University was the institution with the greatest number of publications and cited times. Among all authors, Selkoe DJ was the most influential author with the greatest cited times. The journal of Alzheimer’s disease published the maximum number of documents in the field of synaptic plasticity in AD within 20 years. Furthermore, the results of keywords burst detection showed that the hot topics have shifted from the synaptic transmission, precursor protein and plaque formation to neuroinflammation, microglia and alpha synuclein. Conclusion This study analyzed 2,348 publications with 82,025 references covering the topic of synaptic plasticity in AD and presented the research trends. The results indicated that neuroinflammation, microglia and alpha synuclein were the current research hotspots, which implied the potential clinical applications to AD.